(3EYQH CHjGJ GdLeds - (3YHO Gddg Hf eMeO Hf GdSjO GdHWdjhSj, GHf GdSjO GdHWdjhSj, CHh eMeO J (B521 (3g` s; (3YHO GdQMef Hf ESMGb GdfgGhfOj GdRLGLj, CHh GdbGSe,J (B377 (3g`s ((3CHh GdMSf Ydi Hf CMeO Hf Ydi HfCHi HcQ Gdchai GdTGaYi s)
(3ChdgG (B:s
(3bGd CHh eMeO GdHWdjhSi QMeg Gddg deG aQZJ ef GdcdGe ai GdNdd GdhGbY ai cJGH GdLed CQOJ Cf CJHY Pdc GdcdGe ai EYQGH GHjGJg s
(3BNQgG (B:s
(3hde CLO gPG GdHjJ ajeG WGdYJg ef TYQ GdaQROb aCba efg Ydi MbjbI hGdgd CYde Je GdcJGH s
(3GdfSNI HgG MhGTs
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI edi (B(1 / 328) s
Keywords: (3GdfMhs